2010
DOI: 10.1007/s11259-010-9391-4
|View full text |Cite
|
Sign up to set email alerts
|

Hot air treatment for surface decontamination of table eggs experimentally infected with Salmonella, Listeria, and Escherichia coli

Abstract: Hot-air pasteurization was investigated in the EU-funded project "Reducing Egg Susceptibility to Contaminations in Avian Production in Europe (RESCAPE)" as an innovative treatment for surface bacterial decontamination of table eggs. Possible side effects of the treatment on egg quality traits were also studied. The decontamination power of hot air was evaluated over 1 month on shell eggs that were experimentally inoculated with Salmonella enteritidis, Escherichia coli, or Listeria monocytogenes. The S. Enterit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…In this study, a Salmonella survival with a constant load was observed on packed eggs, whereas 1 log reduction of the Salmonella load was observed in nonpacked ones (Pasquah et al, 2010). The E. coli and L. monocytogenes loads on nonpacked eggs showed a fast decrease reaching the detection limit concentration after 15 and 10 d of storage, respectively , whereas in the present study E. coli grew with a 1 log increase and L. monocytogenes survived on packed eggs.…”
Section: I Discussioncontrasting
confidence: 51%
“…In this study, a Salmonella survival with a constant load was observed on packed eggs, whereas 1 log reduction of the Salmonella load was observed in nonpacked ones (Pasquah et al, 2010). The E. coli and L. monocytogenes loads on nonpacked eggs showed a fast decrease reaching the detection limit concentration after 15 and 10 d of storage, respectively , whereas in the present study E. coli grew with a 1 log increase and L. monocytogenes survived on packed eggs.…”
Section: I Discussioncontrasting
confidence: 51%
“…Manfreda et al [85] Hot air oven, 55 Steam is applied to the eggs as they go through a thermal trap, a partly enclosed room filled with steam Salmonella enterica serovar Typhimurium 8 log CFU per egg -No harmful influences on HU, yolk and albumen pH, and albumen whip were observed. -With a short treatment of a few seconds in the thermal trap prototyped completely inactivated Salmonella (>7.8 log CFU reduction).…”
Section: Methods Types Of Contamination Effect On Egg Properties/deco...mentioning
confidence: 99%
“…Some of the approaches to prevent infection by Salmonella include treatment of edible substances such as poultry and poultry products, and contact surfaces by heat or pulsed light (Haughton et al, 2011;Keklik et al, 2010;Neetoo & Chen, 2011). Chemical treatment with the use of chemicals such as trisodium phosphate, acidified sodium chlorite, citric acid, lactic acid, peroxy acids or gaseous ozone is yet another common approach (Bialka & Demirci, 2007;Lecompte et al, 2009;Manfreda et al, 2010). Tomatoes have been disinfected using chlorine dioxide (Trinetta et al, 2010).…”
Section: Methods For Prevention Of Salmonellosismentioning
confidence: 99%